COMPARISON OF THE ANTIBACTERIAL EFFECTIVENESS OF RED BETEL EXTRACT WITH BLACK BETEL EXTRACT ON Porphyromonas gingivalis BACTERIA - Herryawan Herryawan; Badi Soerachman; Sarah Andintama Gustimuda Chaeruddin (Fakultas Kedokteran Gigi Unjani, 2023)
Periodontitis is a chronic inflammatory disease of the tooth-supporting structures of the teeth caused by a group of specific microorganisms in dental plaque. Porphyromonas gingivalis (Pg) is a bacterium that causes periodontitis found in subgingival plaque. Antibacterial agents are needed as additional therapy to complete mechanical treatment, the main therapy for periodontitis treatment. Red betel (Piper crocatum) and black betel (Piper betle L. var nigra) are herbal plants with active compounds of flavonoids, alkaloids, saponins, tannins, phenols, and essential oils. These compounds are known to act as antibacterial and anti-inflammatory agents. This study aimed to compare the inhibition of red betel leaf extract and black betel leaf extract on the growth of Pg bacteria. This research method is experimental with an in vitro Post Test Only Control Group design. The study was conducted using the disc diffusion method in 10 groups, namely red betel leaf extract concentrations of 25%, 50%, 75%, 100%, black betel leaf extract concentrations of 25%, 50%, 75%, 100%, metronidazole as a positive control, and sterile distilled water as a negative control. Repetition was done thrice in each group on Mueller-Hinton Agar (MHA) media. The results showed that both types of betel leaf extract at all concentrations had antibacterial effectiveness against Pg bacteria. The higher the extract concentration, the more effective bacteria inhibition is. Betel leaf extract with a concentration of 100% had the highest inhibition zone, which is 25.16 mm for red betel and 19.65 mm for black betel. These results indicate that red betel leaf extract has better effectiveness than black betel leaf extract. DOI : 10.54052/jhds.v3n1.p53-68